Proton gradients from light-harvesting E. coli control DNA assemblies for synthetic cells - Jahnke, Kevin; Ritzmann, Noah; Fichtler, Julius; Nitschke, Anna; Dreher, Yannik; Abele, Tobias; Hofhaus, Götz; Platzman, Ilia; Schröder, Rasmus R.; Müller, Daniel J.; Spatz, Joachim P.; Göpfrich, Kerstin (Nature Communications, 2021)
Bottom-up and top-down approaches to synthetic biology each employ distinct methodologies with the common aim to harness living systems. Here, we realize a strategic merger of both approaches to convert light into proton gradients for the actuation of synthetic cellular systems. We genetically engineer E. coli to overexpress the light-driven inward-directed proton pump xenorhodopsin and encapsulate them in artificial cell-sized compartments. Exposing the compartments to light-dark cycles, we reversibly switch the pH by almost one pH unit and employ these pH gradients to trigger the attachment of DNA structures to the compartment periphery. For this purpose, a DNA triplex motif serves as a nanomechanical switch responding to the pH-trigger of the E. coli. When DNA origami plates are modified with the pH-sensitive triplex motif, the proton-pumping E. coli can trigger their attachment to giant unilamellar lipid vesicles (GUVs) upon illumination. A DNA cortex is formed upon DNA origami polymerization, which sculpts and deforms the GUVs. We foresee that the combination of bottom-up and top down approaches is an efficient way to engineer synthetic cells.
Gesehen am 15.10.2021